Comparative study on structural behaviour of bonded and unbonded post-tenseoned beam - Md Noor, Nurazuwa (2006)
In this study, a simple computer program are written using FOTRAN 90 to investigate the behavior of simply supported beam constructed with straight tendon which are subjected to three different load cases. Considering the same stresses applied, beam subjected to loading at one third span shows a less deflection than other load cases. Behavior due to the deflection of bonded tendon gave better performance than unbonded tendon. However, beams with larger span-to-depth ratio would require deviators in case of external prestressing to achieve the desired performance. Parabolic and trapezoidal tendon allows the prestressed beam to carry heavier loads because of the balancing effects of the vertical component of the prestressing deflected tendon. Hence it will required less prestressing force at the mid span compared with the force required in the straight tendon.